Analisis Kenaikan Harga dan Kelangkaan Sembako terhadap Pertumbuhan Perekonomian Masyarakat: Studi Kasus di Dusun Suren Desa Tepos Kecamatan Banyuglugur Kabupaten Situbondo - Vita Nur Sihinda; Ahmad Hafas Rasyidi; Agusti Agusti (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
Sembako is an abbreviation of nine basic ingredients, and sembako is an essential need for daily life, and sembako is needed for the needs of the community, from low to middle and high economic classes. The formulation of the problem of this study is to determine the increase in the price of basic necessities on the economic growth of rural communities. And to determine the scarcity of basic necessities on the economic growth of rural communities. The purpose of this study is to determine the impact of price increases and scarcity of basic necessities on the economic growth of the community in Suren Hamlet, Tepos Village. In this study, the author uses quantitative research methods. The data collection method involves distributing questionnaires using a proportional random sampling approach. The results of the study indicate that the variables Price Increase and Scarcity of Basic Necessities have a positive and significant impact on the economic growth of the community. The t-value for the Price Increase variable is 2,198, while the significance value is 0.031 < 0.05, which indicates that the variable X1 (Price Increase) has an effect on the variable Y (Community Economy). The t-value for the variable Scarcity of Basic Necessities is 4,388, while the significance value is 0.001 < 0.05, which indicates that the variable X2 (Scarcity of Basic Necessities) has an effect on the variable Y (Community Economy). The limitation in this study is the lack of understanding of some members of the community regarding the procedures for filling out the questionnaire.